Regarding to colonial and republican immovable heritage: Casa Muga in Lambayeque - Pareja de Gatti, Piedad (2009)
Regarding to Colonial and Republican immovable heritage: We will talk abotll the Casa Muga in Lambayeque, in four sections. A short summary of Lambayeque's monumental area offers a panoramic view of the historical centre and an approximate idea of its present potential value-partly related to the Royal Tombs Museum (Museo de Tumbas Reales)as a tourist attraction. The project for the Casa Muga's reconstruction describes a series of details and a succession of episodes that make up the history of a monument and that of its revaluation. The specific legislation on immovable historical beritage contains an updated summarized list of the regulations that are supposed to protect it, but that, in fact, turn it into a burden. In other regulations on immovable historical heritage we include those corresponding to civil service, municipalities housing and tourism –in what refers to historial heritage- that, if obeyed, would favorr its restaration, but that in practice are partially run and only if the administrator knows them and how to value them. A few final reflections are included. Though they may be somewhat general, they collect the concern and hope that we perceived in the neighbors of Lambayeque’s monumental are regarding its destiny